Characterization of metabolic syndrome among diverse Hispanics/Latinos living in the United States: Latent class analysis from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). (1st April 2015) - Arguelles, William; Llabre, Maria M.; Sacco, Ralph L.; Penedo, Frank J.; Carnethon, Mercedes; Gallo, Linda C.; Lee, David J.; Catellier, Diane J.; González, Hector M.; Holub, Christina; Loehr, Laura R.; Soliman, Elsayed Z.; et al.
Abstract: Background/objectives: Empirical investigation of the adequacy of metabolic syndrome (MetS) diagnostic criteria, and whether meaningful subtypes of MetS exist, is needed among Hispanics/Latinos. Methods: In 15, 825 US Hispanics/Latinos from HCHS/SOL, latent class analysis of MetS components (waist circumference, systolic and diastolic blood pressure, HDL cholesterol, triglycerides, glucose, and antihypertensive, lipid- and glucose-lowering medication use) was used to investigate (1) whether distinct subtypes of MetS could be identified, and how component levels differed between them, and (2) how identified subtypes related to covariates and cardiovascular disease (CVD) prevalence. Results: Two latent clusters emerged in both men (n = 6317) and women (n = 9508): one characterized by relatively healthy mean levels (Non-MetS cluster, 77.1% of men and 67.1% of women) and the other by clinically elevated mean levels (MetS cluster, 22.9% of men and 32.9% of women) across most MetS components. These clusters showed expected associations with covariates and CVD prevalence. Notable results suggest that (1) HDL cholesterol may poorly differentiate between US Hispanics/Latinos with and without MetS (mean = 45.4 vs. 44.6 mg/dL for men and 51.3 vs. 52.0 mg/dL for women in the MetS vs. Non-MetS clusters, respectively) and (2) the NCEP-ATP III 88 cm waist circumference cutoff for US females may not optimize diagnosis among Hispanic/Latino women (MetS cluster mean waist circumference = 102.5 cm). Conclusions: Beyond classification into having MetS or not, additional subtypes of MetS do not clearly emerge in US Hispanics/Latinos. Current diagnostic cutoffs for some components may not optimize MetS identification among this population. Highlights: We examined metabolic syndrome presentation in Hispanics using latent cluster analysis. 2 clusters emerged in men and women: metabolic syndrome and no metabolic syndrome. HDL cholesterol may not differentiate Hispanics with and without metabolic syndrome. Current criteria may not optimize metabolic syndrome diagnosis among U.S. Hispanics.